Field and Ecology Approaches to Journalism Innovation: The Role of Ancillary Organizations. (18th November 2019) - Lowrey, Wilson; Sherrill, Lindsey; Broussard, Ryan
ABSTRACT: This study assesses the roles played by journalism support organizations or "ancillary" organizations – professional associations, training centers, foundations, labs – in the dynamics of journalism innovation, from the perspectives of field theory and ecology theory. Innovation in data and computational journalism serves as the study's case example. The roles played by ancillary organizations within a changing, complex journalism space are increasingly important, and understudied. Both field and ecology approaches describe ancillary organizations as agents of innovation, but they explain the dynamics differently. Field approaches assume ancillary organizations "consecrate" innovations, and that innovations result from oppositional stances to established practices. Ecology approaches assume ancillary organizations foster interaction, which leads to shared ideas about innovation. The study is based on interviews with various agents in the data journalism space, including working data journalists and ancillary organization leaders. Findings suggest both field and ecology theories are helpful in explaining the innovation process. Field theory is especially helpful for explaining the structural contexts and strategy of innovation, while ecology approaches take a more organic approach, shedding light on the role of human interaction in the adaptation, change and growth of innovation.